Journal of Contemporary Private Law’s Presentation and General Editorial Guidelines - Otavio Luiz Rodrigues Jr. (Revista de Direito Civil Contemporâneo, 2022)
Journal of Contemporary Private Law’s Presentation and General Editorial Guidelines